The Justiciability of Cabinet Appointments in South Africa - Molefhi S Phorego; Hendrik J van As (Obiter, 2024)
For most democracies, Cabinet appointments form part of a plethora of powers that are entrusted to the President alone. Courts are naturally cautious about interrogating the exercise of the power. In South Africa, courts confine themselves to the narrower legal question of how the power was exercised, not whether the President’s decision was correct or incorrect. This is because the courts are wary of second-guessing the decisions of other branches of government, lest they fall foul of the doctrine of separation of powers. This article probes the President’s power to appoint Cabinet members, and whether a court may set aside any unlawful exercise of the power without encroaching on the separation of powers. Owing to inadequate political oversight mechanisms over Cabinet appointments, the President’s power is too broad and should be curtailed to enhance accountability for the exercise of the power. To this extent, the President’s appointment of Cabinet members should be subject to parliamentary confirmation.